Honey in The Management of Diabetic Foot : A Review of The Literature - Nurul Azmawati Mohamed @ Abd Aziz; Mohd Asha'ari Bain; Nur Iffah Illani Binti Mohamed Rasidi; Shalinawati Ramli (Penerbit USIM, 2024)
Indexed by MyCite